Transformasi Evaluasi Pembelajaran PAI berbasis Digital: Optimalisasi Media Quizizz sebagai Alat Ukur Adaptif - Magfirah, Innayatul; Afiyati, Fudla; Bashith, Abdul (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
Digital transformation in the world of education has driven innovation in learning evaluation methods, including in Islamic Religious Education (PAI). This study aims to examine the use of the Quizizz application as an adaptive measuring tool in evaluating PAI learning. By using a literature review study approach such as from several journals or books or other references. The results of the study show that Quizizz is able to increase student participation, provide instant feedback, and adjust the level of difficulty of questions based on the abilities of the participants. In addition, this platform supports more interactive and enjoyable learning without reducing the essence of cognitive or affective assessment in PAI. Optimizing Quizizz also helps teachers analyze learning outcomes quickly and accurately. In conclusion, digitalization of evaluation through Quizizz is an effective strategy for creating adaptive, efficient, and relevant evaluations to the needs of the digital generation.